Analisis Wacana Kritis Pemberitaan Pembubaran FPI di Media Online - Fitri Fitri; Alifa Nur Fitri; Silvia Riskha Fabriar (IQTIDA : Journal of Da'wah and Communication, 2021)
This study intends to describe the structure of the text in the news of the Disbandment of FPI: DPR's Attitude, NU and Muhammadiyah Responses to Rizieq's Instructions on Tribunnews.com and Prohibited in NKRI All FPI activities will be stopped on Detik.com. This research is a qualitative descriptive study. The data collection method is done by library research. The data were analyzed based on the critical discourse analysis of Teun A. Van Dijk. The results showed that the structure of the text on Tribunnews.com and Detik.com agreed with the dissolution of FPI by the government. The social cognition of the two online media displays group and institutional knowledge, while at the level of the social context Tribunnews.com and Detik.com contain the practice of power and access with the actors, namely the government and FPI as community organizations.